REDUCING CARBON FOOTPRINT IN AN OEM SUPPLY CHAIN CAUSED BY INADEQUATE INTERPRETATION OF X-RAY RESULTS OF HIDDEN DEFECTS IN DUCTILE IRON CASTINGS - Pavlin, Tadej; Brinovar, Iztok; Stergar, Bojan; Praunseis, Zdravko (Journal of Energy Technology, 2023)
In the global market, the casting industry recorded a growth trend for ductile iron last year. Ductile iron is used due to its excellent mechanical properties, machinability and castability. The microstructure of nodular cast iron consists of a metal matrix and graphite extruded in the form of beads and nodules. In recent years, the production of ductile iron castings has increased significantly for parts for heavy transport vehicles and containers for permanent disposal of nuclear waste, and it is expected that this trend of expansion will continue for at least the next twenty years. When poured in sand moulds, the quality of products can not be reached. There can be defects on the raw surface and/or on the machining surface, as well as hidden defects inside the material. For casting products, defects can be detected on raw and machining surfaces and inside material defects by carrying out a visual inspection. The results of the inspection depend on the inspection method used. In general, basic methods of cutting or milling inspection are used in the casting industry, which means that products are classified in terms of whether or not they meet the drawing specification(s). The authors of this paper focused on the hidden defects inside ductile iron material, which can be detected by carrying out a cutting or milling inspection or through an X-ray inspection. Huge amounts of energy and energy sources are used in the production of nodular cast iron, which creates a negative environmental footprint. Therefore, by being preventively rational and through appropriate control procedures it is possible to significantly reduce the carbon footprint.
Keywords: carbon footprint; ductile iron; X-ray inspection; cutting inspection; hidden mistakes; defects; porosity; inclusion; green energy; reduction in energy production